Evidence that the penton base of adenovirus is involved in potentiation of toxicity of Pseudomonas exotoxin conjugated to epidermal growth factor. - Seth, P (1984)
When KB cells are incubated for 1 h with human adenovirus type 2 or type 5 (1 microgram/ml) and a conjugate of epidermal growth factor and Pseudomonas exotoxin (EGF-PE), protein synthesis is inhibited by 80 to 90%. Under these conditions, neither adenovirus nor EGF-PE alone has any effect on host protein synthesis. Thus, adenovirus enhances the toxicity of EGF-PE. A number of antibodies to intact virus and capsid components were tested for their ability to block the enhancing activity and virus uptake. At appropriate dilutions, antibodies prepared against intact virus and penton base blocked the enhancing activity without affecting virus uptake. Antibodies against hexon and fiber blocked virus uptake and enhancing activity in parallel. These studies suggest that the penton base is important in lysis of the vesicles which contain adenovirus and EGF-PE, and this base allows virus and toxin to enter the cytoplasm.